2019
DOI: 10.3390/molecules24112087
|View full text |Cite
|
Sign up to set email alerts
|

Chitinases as Food Allergens

Abstract: Food allergies originate from adverse immune reactions to some food components. Ingestion of food allergens can cause effects of varying severity, from mild itching to severe anaphylaxis reactions. Currently there are no clues to predict the allergenic potency of a molecule, nor are cures for food allergies available. Cutting-edge research on allergens is aimed at increasing information on their diffusion and understanding structure-allergenicity relationships. In this context, purified recombinant allergens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
(38 reference statements)
0
19
0
3
Order By: Relevance
“…Plant chitinases are also a well-known group of food allergens. It is a relatively small group, but it is present in highly consumed fruits [75]. Chitinases can be divided into five classes (I-V), and plant class III chitinases (PR-8 proteins) have an additional lysozyme activity, which is not found in other classes of chitinases [76].…”
Section: Chitinase III As Allergen In Raspberrymentioning
confidence: 99%
“…Plant chitinases are also a well-known group of food allergens. It is a relatively small group, but it is present in highly consumed fruits [75]. Chitinases can be divided into five classes (I-V), and plant class III chitinases (PR-8 proteins) have an additional lysozyme activity, which is not found in other classes of chitinases [76].…”
Section: Chitinase III As Allergen In Raspberrymentioning
confidence: 99%
“…Zhao et al [ 19 ] indicated chitinase and paramyosin as two other potential allergens. Chitinase has already been discussed as an allergen between different species, especially in plant kingdom, like fruits [ 42 ]. AK from silkworm (SW) is of particular relevance because it is the only allergen (Bomb m 1) from edible insects officially accepted as food allergen ( www.allergen.org ) and included in the IUIS allergen database.…”
Section: Cross-reactivity and Primary Sensitizationmentioning
confidence: 99%
“…These findings indicate that further efforts are still needed to achieve a robust characterization of allergenic chitinases (and also of all the other allergens). 17…”
Section: Characterization Of Allergensmentioning
confidence: 99%